Aminooxyacetic acid hemihydrochloride inhibits osteoclast differentiation and bone resorption by attenuating oxidative phosphorylation - Yang, Biao; Su, Yuangang; Han, Shuai; Chen, Runfeng; Sun, Ran; Rong, Kewei; Long, Feng; Teng, Hailong; Zhao, Jinmin; Liu, Qian; Qin, An (Frontiers in Pharmacology, 2022)
Osteoclasts undergo active metabolic reprogramming to acquire the energy needed during differentiation and bone resorption. Compared with immature osteoclasts, mature osteoclasts comprise higher levels of electron transport chain enzymes and more metabolically active mitochondria. Of all energy metabolism pathways, oxidative phosphorylation is considered to be the most efficient in supplying energy to osteoclasts. We found that the malate-aspartate shuttle inhibitor aminooxyacetic acid hemihydrochloride inhibits osteoclastogenesis and bone resorption by inhibiting exchange of reducing equivalents between the cytosol and the mitochondrial matrix and attenuating mitochondrial oxidative phosphorylation in vitro. The weakening of the oxidative phosphorylation pathway resulted in reduced mitochondrial function and inadequate energy supply along with reduced reactive oxygen species production. Furthermore, treatment with aminooxyacetic acid hemihydrochloride helped recover bone loss in ovariectomized mice. Our findings highlight the potential of interfering with the osteoclast intrinsic energy metabolism pathway as a treatment for osteoclast-mediated osteolytic diseases.